Association between time of day differences in muscle force production and the post-translational modification (Phosphorylation) of muscle proteins - Zulezwan Ab Malik (Tanjong Malim, 2018)
Association between time of day differences in muscle force production and the post-translational modification (Phosphorylation) of muscle proteins by Zulezwan Ab Malik